Tool path generation algorithm and 3D tolerance analysis for free-form surfaces - Suresn Baou, \/; Raviswaran, N (Ethiopian Journal of Science and Technology, 2024)
This paper focuses on developing algorithm that generates tool paths for. free-form surfaces based on the accuracy of a desired manufaciured part. A manufacturing part is represented by mathematical curves and surtaces. Using the mathematical representation of the manufacturing part. we generate reliable and near optimal tool paths as well as cutter location data file for post - processing. This algorithm includes two components. First is the forward-step function which determines the maximum distance, called forward step, between iwo cutter contact points with a given tolerance. This function is independent of the surface type and is applicable to all continuous parametric surfaces that are twice differentiable. The second component is the side-step function which determines me maximum distance, cailed side-step, between two adjacent tool paths with a given scallop height. This algorithm reduces manufacturing and computing time as well as the cutter - contact points while keeping the given tolerance and scallop height in the tool paths. The parts for which the cutter contact points are generated using the proposed algorithm. are machined using a three axes milling machine. As part of the validation process. the tool paths generated during machining are analyzed to compare the machined part and the desired part.